mGluR1 Receptors Contribute to Non-Purinergic Slow Excitatory Transmission to Submucosal VIP Neurons of Guinea-Pig Ileum - Foong, Jaime Pei Pei; Bornstein, Joel C. (Frontiers in Neuroscience, 2009)
Vasoactive intestinal peptide (VIP) immunoreactive secretomotor neurons in the submucous plexus are involved in mediating bacterial toxin-induced hypersecretion leading to diarrhoea. VIP neurons become hyperexcitable after the mucosa is exposed to cholera toxin, which suggests that the manipulation of the excitability of these neurons may be therapeutic. This study used standard intracellular recording methods to systematically characterize slow excitatory postsynaptic potentials (EPSPs) evoked in submucosal VIP neurons by different stimulus regimes (1, 3 and 15 pulse 30 Hz stimulation), together with their associated input resistances and pharmacology. All slow EPSPs were associated with a significant increase in input resistance compared to baseline values. Slow EPSPs evoked by a single stimulus were confirmed to be purinergic, however, slow EPSPs evoked by 15 pulse trains were non-purinergic and those evoked by 3 pulse trains were mixed. NK1 or NK3 receptor antagonists did not affect slow EPSPs. The group I mGluR receptor antagonist, PHCCC reduced the amplitude of purinergic and non-purinergic slow EPSPs. Blocking mGluR1 receptors depressed the overall response to 3 and 15 pulse trains, but this effect was inconsistent, while blockade of mGluR5 receptors had no effect on the non-purinergic slow EPSPs. Thus, although other receptors are almost certainly involved, our data indicate that there are at least two pharmacologically distinct types of slow EPSPs in the VIP secretomotor neurons: one mediated by P2Y receptors and the other in part by mGluR1 receptors.